Preliminary Design Study of Thorium(Th) and Protactinium ( 231 Pa) Based Fuel for Tight Lattice Long Life BWR - Eka Sapta Riyana; Zaki Su’ud (Institut Teknologi Bandung, 2005)
A preliminary design study for the utilization of thorium based fuel loaded with 231Pa on tight lattice BWR type reactor has been performed. Protactinium-231 has very interesting neutronic properties, which enable the core to reduce initial excess-reactivity and simultaneously increase production of 233U to 231Pa in burn-up process. Optimizations the content of 231Pa in the core enables the BWR core to sustain enough reactivity for long period of time with reasonable burn-up reactivity swing. Based on the optimization of fuel element composition (Th and Pa) in low moderation environment (tight lattice core) can be achieved reactor core with longer operation time, 20 30 years operation without fuel shuffling or refueling, with average power densities of about 35 watt/cc.